Person-organization fit and turnover intention: the mediating role of meaning in work and moderating effect of independence ethical climate among polish employees - Wnuk, Marcin; Chudzicka-Czupała, Agata (Frontiers in Psychology, 2026)
ObjectiveBased on the job demands–resources (JD-R) theory and the person–organization (P–O) fit concept, this paper verified whether employees’ perception of the congruency of their values with those of their organization is directly and indirectly related to their turnover intentions through meaning in work. Additionally, this paper investigated whether an ethical climate of independence moderates the link between P–O fit and meaning in work.MethodThis cross-sectional study was conducted among 1,071 employees of companies of different sizes in Poland. Participants completed validated measures assessing P-O fit, five types of ethical climate (independence, caring, instrumental, law and code, and rules), meaning in work, and turnover intention. A moderated mediation model was tested using Hayes’ PROCESS macro (Model 7), controlling for demographic and organizational variables. Confirmatory factor analysis established discriminant validity of the constructs.ResultsThe study confirmed direct and indirect mechanisms linking P-O fit to turnover intention. P-O fit was negatively related to turnover intention both directly (b = −0.26, p < 0.001) and indirectly through meaning in work. Crucially, independence ethical climate significantly moderated the P-O fit to meaning in work relationship, such that the positive effect of value congruence on meaningful work was stronger when employees perceived greater freedom to base ethical decisions on their personal moral standards. The moderated mediation index was statistically significant, confirming that the indirect effect of P-O fit on turnover intention through meaning in work varied across levels of independence ethical climate.ConclusionP-O fit facilitates meaning in work and protects employees from motivation to quit the organization, particularly when organizations cultivate independence ethical climates. Ethical decisions rooted in employees’ personal moral codes amplify the positive link between P-O fit and meaning in work, which serves as an important antecedent of retention. Practical implications include the importance of values-based recruitment, creating ethical climates that honor individual moral autonomy, and implementing interventions to enhance meaning in work.